Evaluation of the program nespresso aaa and their impact in the sostenibilidad of the caficultura - Gómez Paz, Diego Fernando; Zarama A., Manuel Fernando; Navia E, Jorge Fernando (Revista de Ciencias Agrícolas, 2009)
The present study was carried out in the municipality of the Union, located to the nororiente of the department of Nariño, located at 1° 26’ 06" North latitude and 77° 80’ 15" longitude West. With objective of analyzing participativamente the sostenibilidad and the quality of coffee properties under the methodology of Nespresso AAA. For that which you applies a sampling stratified at random, using the tool TASQ which generate information of practical in the properties, by means of interviews, and you visit to properties. The methodology AMOEBA was also used, for the integration and comparison of the approaches and indicators. The main results demonstrated that the caficultura of the region is heterogeneous with regular properties and other more tecnificadas, compared with of the structure of Nespresso. Of the four levels of the program, three groups were identified, level faulty 48%, in level basic 43%, in level emergent 9%, and in advanced level there was not any property. The integration of the indicators evidenced that the properties are weak in the social and economic, on the other hand the indicators of quality and environmental they reported better practices. As well as you presents the impact of a property studied among the periods 2007 and 2008 achievement to advance from level faulty 42% to level basic 53%. Passwords: sostenibilidad, quality, NESPRESSO AAA, stratified sampling, tool TASQ, approaches, indicators.